AB0134 Blood lymphocyte subsets according to the clinical profile in SJÖGREN'S syndrome. (15th June 2017) - Barcelos, F; Martins, C; Nunes, G; Lopes, T; Patto, J Vaz; Amaral, J; Branco, JC; Borrego, LM
Abstract : Background: It has been recently described the occurrence of disturbances in lymphocyte subsets in Sjögren's syndrome (SS) which may reflect B cell hyper activation and a T cell adjuvant role. Objectives: We aim to characterize circulating lymphocyte subsets in SS patients, according to disease activity and antibody profile. Methods: We have included in this study 53 SS patients (2002 AECG criteria) of which 22 with >10 years since diagnosis and 31 with <2 years since diagnosis, and 22 healthy controls. Lymphocyte subsets, including follicular (Tfh) and regulatory T (Treg) cells, maturation subsets, plasmablasts (PB) and regulatory B (Breg) cells, were characterized by flow cytometry. Statistical analysis was performed with GraphPad. Significance was considered for p<0.05. Results: Compared to controls, SS patients had lower absolute counts of B (p=0.0337) and T cells (p=0.0012), lower CD4 (p=0.0002) and higher CD8 percentages (p=0.0006), resulting in an increased CD4/CD8 ratio (p=0.0006). Additionally, there was decrease in absolute counts of Tregs (p=0.0008) and Th17 cells (p=0.0005) in SS patients. Moreover, there was a decreased absolute counts (p<0.0001) of Tfh cells, identified by CXCR5 expression, though higher levels of IL21 + CD4 T cells (p=0.0209) and Tfh1 cells (p=0.0092). SS patients also presented higher % of naïve B cells (p=0.0412), lower % and absolute counts of memory (%, p=0.0161; abs p=0.0002) and unswitched memory (%, p=0.0106; abs p=0.0005) B cells and lower absolute counts (p=0.0001) of switched memory B cells, with higher naive/memory B cell ratios, compared to healthy subjects (p=0.0219). Accordingly, using the Bm1–5 classification, we have found decreased Bm1 (%, p=0.0087; Abs, p=0.0007), eBm5 (Abs, p=0.0005) and Bm5 cells (Abs, p=0.0015) in SS patients. Similar Bm2+Bm2'/eBm5+Bm5 ratios were observed in patients and controls. CD24 + CD27 + Bregs were also decreased (p≤0.0012) in SS patients. SS patients had also an increase in IL21 + CD4 T cells, particularly in patients with extra-glandular manifestations (EGM) (n=12), who also presented less Tfh17 cells (p=0.0409) comparing to patients without EGM. PB were decreased in patients with EGM only when compared to controls (p=0.0434). SSA + patients (n=36) had more frequently EGM than SSA -, higher ESSDAI score, γ-globulin levels and lower salivary flow. Compared to SSA - and controls, increased IL21 + CD4 T cells were detected in SSA + patients (p≤0.0284), who also had higher Tfh1 cells than controls (p≤0.0065). Lower Bm1 cells (p≤0.0305) were observed in SSA + patients compared to SSA - and controls, with an increase % of Bm3+Bm4 cells (p=0.011) compared to SSA - . Conclusions: The immune profile of SS patients has distinctive features, with decreased memory B cell subsets, including CD24 + CD27 + Bregs. Moreover, an increased capacity of IL21 secretion by T cells, together with a more prominent Tfh1 signature seem to be the hallmark of SS, particularly in patients with EGM and autoantibody production, suggesting an immune environment prone to proinflammatory processes, in severe patients. Comprehending the immune dynamics in SS may be valuable for diagnosis, follow-up and future therapeutic decisions. Disclosure of Interest: None declared